2021
DOI: 10.1080/09669582.2021.1879818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crisis on crisis management practices: a case from Turkish tourism enterprises

Abstract: Crises are broadly thought to damage the tourism industry by decreasing tourism revenues due to reduced inbound tourism. This study investigated the negative short-term effects of crises on the crisis management practices of tourism enterprises in Turkey following terrorist attacks between 2015 and 2016, political tensions with the Russian Federation after a military aircraft was shot down in 2015, and the attempted coup in 2016. 219 valid questionnaires were obtained from representatives and managers of hotel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…While the tourist perspective has to date dominated the discussion around COVID-19 recovery (Bausch et al, 2020), we explored the central role that FLEs play during crises given that the tourism industry is extremely dependent on well-trained and qualified employees in running their operations. This research highlighted the importance of developing human resource management strategies which might be able to mitigate or even avoid the impact of crises on FLEs (Ertaş et al, 2021). Therefore, this study showed how events gradually triggered employees' sensemaking and interorganizational measures during the COVID-19 crisis in the tourism and hospitality industry.…”
Section: Conclusion and Recommendationsmentioning
confidence: 79%
“…While the tourist perspective has to date dominated the discussion around COVID-19 recovery (Bausch et al, 2020), we explored the central role that FLEs play during crises given that the tourism industry is extremely dependent on well-trained and qualified employees in running their operations. This research highlighted the importance of developing human resource management strategies which might be able to mitigate or even avoid the impact of crises on FLEs (Ertaş et al, 2021). Therefore, this study showed how events gradually triggered employees' sensemaking and interorganizational measures during the COVID-19 crisis in the tourism and hospitality industry.…”
Section: Conclusion and Recommendationsmentioning
confidence: 79%
“…Despite government assistance programs, due to the accumulating financial problems of enterprises, we assume an increase in the number and value of non-performing loans in the aftermath of the COVID-19 pandemic (Ertaş et al, 2021;Liu et al, 2020). We put forward the following research hypothesis.…”
Section: Methodsmentioning
confidence: 99%
“…Beck et al (Beck et al, 2015), using panel data from 75 countries worldwide, reveal that share of non-performing loans substantially increase during global financial crisis 2008-2009. Ertas et al (Ertaş et al, 2021), based on the data about Turkish enterprises, show that entrepreneurs face difficulties in repaying and recovering loans during crisis periods. Liu et al (2020) also reveal that non-performing loans of EU and BRICS countries have substantially increased after the global financial crisis 2008-2009. Our contribution is that we are the first to examine the impact of COVID-19 on the market of loans granted to micro-entrepreneurs and farmers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 65% of the professional associations that canceled an event lacked sufficient insurance coverage to offset the costs incurred by that cancellation (West and Whedbee, 2020). Facing prohibitions on holding annual gatherings and other face-to-face activities that would normally generate substantial portions of their total revenue, organizations tended to make budgetary changes (Ertaş et al , 2021). However, to develop sustainable revenue sources rather than constantly focusing on budget-cutting measures or staff reductions, professional associations must identify what impact they can have on their members and the broader communities they serve (Hager, 2014; Wang and Ki, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As the hospitality and tourism industry is not immune to external factors beyond the pandemic, such as natural disasters, economic recession and terrorism, studies on recovery strategies and crisis and risk management have been conducted in a wide range of contexts: financial recovery strategies for restaurants (Yost et al , 2021), crisis management practices among tourism enterprises (Ertaş et al , 2021) and recovery marketing after crises in the tourism industry (Orchiston and Higham, 2016). However, there is a paucity of research on crisis management for the event industry, particularly concerning the role of professional associations.…”
Section: Introductionmentioning
confidence: 99%